DATA NETWORKING SUPPORT SERVICES OF PUSHCHINO RADIOASTRONOMY OBSERVATORY, ASTROSPACE CENTER OF LEBEDEV PHYSICAL INSTITUTE - Dumsky, D. V.; Isaev, E. A.; Samodurov, V. A.; Likhachev, S. F.; Shatskaya, M. V.; Kitaeva, M. A.; Zaytcev, A. Yu.; Ovchinnikov, I. L.; Kornilov, V. V. (Одеські астрономічні публікації, 2014)
Growth of local area network Observatory associated with employee needs to access network resources has led to an increase in the number of computing and network devices. Until recently, we tested performance of these systems excellent manual and most of the problems and faults detected already on the fact the accident occurred. For a small number of network nodes, manual monitoring is not a signiﬁcant problem, but with increasing the number of nodes troubles hooting becomes a very diﬃcult task for network and system administrators and outage in work of network services Observatory may becomes critical. There fore there was a need to automate the monitoring service network resources and servers.